2005
DOI: 10.1111/j.1365-2621.2005.tb11460.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pectinmethylesterase Infusion Methods and Processing Techniques on Strawberry Firmness

Abstract: Further reproduction without permission is prohibited S: Sensory & Nutritive Qualities of Food JFS S: Sensory and Nutritive Qualities of Food , v , v , v , vacuum-assisted infusion of PME and calcium could acuum-assisted infusion of PME and calcium could acuum-assisted infusion of PME and calcium could acuum-assisted infusion of PME and calcium could acuum-assisted infusion of PME and calcium could limit the portion of firmness loss due to pressure treatment to 30% compared with 80% for non-pretreated fruits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…172 In cases where a (thermal) pretreatment would activate detrimental enzymes or where only low amounts of endogenous PME are present, application of exogenous PME through enzyme infusion can be performed (e.g., the commercial preparation NovoShape from Novozymes). [174][175][176] Formation of calcium-pectin crosslinks may also improve or preserve the viscosity of liquid plant-based products. 177 Third, demethoxylation of pectin reduces its sensitivity to chemical b-eliminative depolymerisation, occurring during heating and associated with heat-induced softening of many fruits and vegetables.…”
Section: Pme In Relation To Texture Of Plant-based Foodsmentioning
confidence: 99%
“…172 In cases where a (thermal) pretreatment would activate detrimental enzymes or where only low amounts of endogenous PME are present, application of exogenous PME through enzyme infusion can be performed (e.g., the commercial preparation NovoShape from Novozymes). [174][175][176] Formation of calcium-pectin crosslinks may also improve or preserve the viscosity of liquid plant-based products. 177 Third, demethoxylation of pectin reduces its sensitivity to chemical b-eliminative depolymerisation, occurring during heating and associated with heat-induced softening of many fruits and vegetables.…”
Section: Pme In Relation To Texture Of Plant-based Foodsmentioning
confidence: 99%
“…The strawberry pieces were immersed in a solution containing 100 U/mL Aspergillus aceleatus PME (Novoshape, Novozymes, Bagsvaerd, Denmark) and 0.5% (w/w) CaCl 2 AE 2 H 2 O and vacuum (10 hPa) was applied for 5 min at room temperature (Duvetter et al, 2005).…”
Section: Pretreatment Conditionsmentioning
confidence: 99%
“…Sila et al, [30] demonstrated that combined effect of high pressure treatment and CaCl 2 treatment improved the texture of carrots during thermal processing. High pressure-assisted infusion of pectin methyl esterase and calcium chloride in strawberry was shown to improve the firmness [13,31]. Mahadevan et al, [32] indicated that high pressure pretreatment increased infusion of quercetin by 3 times into cranberries as compared to untreated ones.…”
Section: Introductionmentioning
confidence: 99%